Direct conversion of cellulose into ethanol and ethyl‐β‐d‐glucoside via engineered Saccharomyces cerevisiae. Issue 12 (21st September 2018) - Jayakody, Lahiru N.; Liu, Jing‐Jing; Yun, Eun Ju; Turner, Timothy Lee; Oh, Eun Joong; Jin, Yong‐Su
Abstract: Simultaneous saccharification and fermentation (SSF) of cellulose via engineered Saccharomyces cerevisiae is a sustainable solution to valorize cellulose into fuels and chemicals. In this study, we demonstrate the feasibility of direct conversion of cellulose into ethanol and a biodegradable surfactant, ethyl‐β‐d ‐glucoside, via an engineered yeast strain (i.e., strain EJ2) expressing heterologous cellodextrin transporter (CDT‐1) and intracellular β‐glucosidase (GH1‐1) originating from Neurospora crassa . We identified the formation of ethyl‐β‐d ‐glucoside in SSF of cellulose by the EJ2 strain owing to transglycosylation activity of GH1‐1. The EJ2 strain coproduced 0.34 ± 0.03 g ethanol/g cellulose and 0.06 ± 0.00 g ethyl‐β‐d ‐glucoside/g cellulose at a rate of 0.30 ± 0.02 g·L −1 ·h −1 and 0.09 ± 01 g·L −1 ·h −1, respectively, during the SSF of Avicel PH‐101 cellulose, supplemented only with Celluclast 1.5 L. Herein, we report a possible coproduction of a value‐added chemical (alkyl‐glucosides) during SSF of cellulose exploiting the transglycosylation activity of GH1‐1 in engineered S. cerevisiae . This coproduction could have a substantial effect on the overall technoeconomic feasibility of theSSF of cellulose. Abstract : Simultaneous saccharification and fermentation (SSF) of cellulose via engineered Saccharomyces cerevisiae s a sustainable solution to valorize cellulose into fuels and chemicals. In this study, we demonstrate the feasibility of direct conversion of cellulose into ethanol and a biodegradable surfactant, ethyl‐β‐d‐glucoside, via an engineered yeast strain (i.e., strain EJ2) expressing heterologous cellodextrin transporter (CDT‐1) and intracellular β‐glucosidase (GH1‐1) originating from Neurospora crassa . We identified the formation of ethyl‐β‐d‐glucoside in SSF of cellulose by the EJ2 strain owing to transglycosylation activity of GH1‐1.